Reading the mind of women landscape architects: A case study of ILAM members - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
Abstract: Since its inception in 1982, the Institute of Landscape Architects has about 289 corporate and graduate members. Out of this, 90 are women, trained at local and foreign universities. How do these female professionals fare against their male counterparts, other design professionals, their clients and their bosses? An informal interview conducted with twenty of these female professionals asking for their views and opinions about the professions and other related works. Many are now at the peak of their career with a few just starting out and feeling the heat of the competition. The findings found that they are treated equally by their male professionals, but have to work doubly hard to prove their worth. This paper will reveal some information about an emerging breed of female professionals. The paper is based on their own account and will provide a helpful insight and guide for future female landscape architects as well as other female design professionals in the field of planning, architecture and interior designers.